Procrastinación académica un análisis de la información del 2010 al 2021: Academic procrastination an analysis of information from 2010 to 2021 - Herrera Falcón, Maria Laura (2023)
The academic procrastination is leaving study-related tasks for a later time that never comes. This article aimed to determine the information that existed on academic procrastination in the period from 2010 to 2021. Journals such as: Revista Iberoamericana de Psicología: Ciencia y Tecnología, Anales de Psicología, Global Journal of Educational Research, Psychological Review, Revista Electrónica Interuniversitaria de Formación del Profesorado, Revista Complutense de Educación, British Journal of Educational Psychology, Researchgate.net, Horizonte de la Ciencia Revista Científica, SciELO, were used with the descriptors procrastination, academic procrastination, procrastination, academic procrastination and postponement of activities; such research was conducted in Spanish and its relative in English. The review showed that academic procrastination occurred in a higher percentage within the university student population. It was concluded that this procrastination does not only occur in a specific gender, but it occurred in both, female and male, and it had nothing to do if the grades are high or low, procrastination occurs in an equivalent way.